A history of the university in Europe. 2 : Universities in early modern Europe 1500-1800 - Symoens, Hilde (Hildegarde), 1943- (Cambridge : Cambridge university press, 1996)
This is the second volume of a four-part history of the university in Europe, written by an international team of authors, which covers the development of the university in Europe (east and west) from its origins to the present day. It focuses not only on the history of individual institutions, nor on the universities in any individual country, but on a number of major themes viewed from a European perspective. The chief originality of this work lies in its comparative, interdisciplinary, collaborative and transnational nature. Volume II looks at the university in Early Modern Europe, and attempts to situate the universities in their social and political context throughout the three centuries spanning the period 1500 to 1800.
Includes bibliographical references and indexes.
Keywords: Education, Higher -- History. -- Europe; Universities and colleges -- History. -- Europe